2017
DOI: 10.18203/2320-6012.ijrms20172446
|View full text |Cite
|
Sign up to set email alerts
|

Study of haematological parameters in malaria

Abstract: Background: Malaria   causing   plasmodia   are   parasites   of   blood   and   hence   induce haematological alterations. The haematological changes that have been reported to accompany malaria include anemia, thrombocytopenia and leucocytosis, leukopenia, mild   to   moderate   atypical   lymphocytosis, monocytosis,   eosinophilia   and neutrophilia.Methods: Total hundred smear positive malaria cases were taken and various hematological parameters and biochemical parameters were studied.Results: Out of 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 9 publications
5
13
3
Order By: Relevance
“…In studies like Yadav RK et al, and Surve KM et al, had similar rates of male: female ratio which is 1.32:1 in both. 7,8 In other studies like Khuraiya P et al, and Patel G et al 9,10 also some near similar rates above studies which are 1.26: 1 and 1.30:1 respectively. Some studies showed very high incidence in males compared to females like Kalavati GP et al, showed a very high male incidence which is more than three times that of the female which is 3.38:1.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In studies like Yadav RK et al, and Surve KM et al, had similar rates of male: female ratio which is 1.32:1 in both. 7,8 In other studies like Khuraiya P et al, and Patel G et al 9,10 also some near similar rates above studies which are 1.26: 1 and 1.30:1 respectively. Some studies showed very high incidence in males compared to females like Kalavati GP et al, showed a very high male incidence which is more than three times that of the female which is 3.38:1.…”
Section: Discussionsupporting
confidence: 66%
“…14 In Another study group Surve KM et al, fever was present in 99% of the patients. 8 But in all study groups, the predominant complaint is fever only. Along with fever, chills and rigors is also a common symptom observed in the majority of studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Malaria could lead to changes in haematological status alongside with other conditions such as anaemia, thrombocytopenia and leukocytosis, leukopenia, lymphocytosis, monocytosis, eosinophilia and neutrophilia (23). Thrombocytopenia is among the major haematological aberrations frequently observed among malaria patients (24).…”
Section: Pathophysiology Of Malaria On Hematological Parameters Changmentioning
confidence: 99%
“…Malaria surveillance for the period from 1995 to 2011 is shown that API (Annual parasite rate) has been steadily declining in India from 3.29 in 1995 to 1.10 in 2011 [2]. Malaria causing plasmodium are parasites of blood and hence induce haematological alterations [3]. The anaemia is caused by excess removal of non-parasitized erythrocytes in addition to immune destruction of parasitized red cells, and impaired compensation for this loss by bone marrow dysfunction [4,5].…”
Section: Introductionmentioning
confidence: 99%